2017
DOI: 10.3389/fneur.2017.00524
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Venlafaxine, Flunarizine, and Valproic Acid in the Prophylaxis of Vestibular Migraine

Abstract: BackgroundDifferent types of medications are currently used in vestibular migraine (VM) prophylaxis, although recommendations for use are generally based on expert opinion rather than on solid data from randomized trials. We evaluated the efficacy and safety of venlafaxine, flunarizine, and valproic acid in a randomized comparison trial for VM prophylaxis.MethodsSubjects were randomly allocated to one of three groups (venlafaxine group, flunarizine group, and valproic acid group). To assess the efficacy of tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 29 publications
1
81
0
3
Order By: Relevance
“…[17,18] In the study of Çeliker et al, valproic acid was found to be effective on the vestibular symptoms of patients with migraine, whereas in another study comparing venlafaxine and flunarizine, the efficacy of valproate on the vestibular symptoms was found to be lower compared to other agents. [19,20] Our case had presented in the attack period with dizziness only, and did not benefit from intravenous dimenhydrinate therapy. However, a rapid response was observed to valproic acid 500 mg oral, which was recommended during prophylactic therapy.…”
Section: Discussionmentioning
confidence: 76%
“…[17,18] In the study of Çeliker et al, valproic acid was found to be effective on the vestibular symptoms of patients with migraine, whereas in another study comparing venlafaxine and flunarizine, the efficacy of valproate on the vestibular symptoms was found to be lower compared to other agents. [19,20] Our case had presented in the attack period with dizziness only, and did not benefit from intravenous dimenhydrinate therapy. However, a rapid response was observed to valproic acid 500 mg oral, which was recommended during prophylactic therapy.…”
Section: Discussionmentioning
confidence: 76%
“…17,18 There are numerous retrospective cohort studies and openlabel trials involving prophylactic medical treatment of VM, with various agents being recommended from guidelines for migraine headache. [19][20][21][22][23][24][25][26] Furthermore, several case series reported treatment effects of less established prophylactic migraine medications including pizotifen, 26 magnesium, 21 butterbur root extract, 21 and drugs usually not often used in migraine such as carbamazepine, 26 lamotrigine, 27 venlafaxine, 24 acetazolamide, 28 cinnarizine, 29 and a combination of cinnarizine and dimenhydrinate. 30 The fact that virtually all of these studies report benefit from oral prophylaxis of VM raises suspicion that what appears to be pharmacological efficacy might be rather due to the placebo effect and spontaneous remission.…”
Section: Pharmacological Prophylaxismentioning
confidence: 99%
“…31 In migraine headache, there is no firm evidence that any of the recommended preventive agents is more effective than others, 14,32 and the same accounts for the pharmacological prophylaxis of VM. 25 Thus, a drug is chosen primarily on the basis of coincidental and comorbid conditions and expected side effects. As a rule, drugs licensed for migraine prophylaxis…”
Section: Pharmacological Prophylaxismentioning
confidence: 99%
“…LTG was also used in 9 patients with prolonged aura symptoms that usually did not respond to any preventative treatment, 2 individuals reported a partial remission and 3 others a complete relief of their attacks . Finally, although metoprolol and flunarizine were usually deemed as the most effective treatment of vestibular migraine, the frequency of attacks was found more than halved in 18 of 19 patients with vestibular migraine who were treated by LTG and a complete relief was even detected in one fourth of them . In a different study, a significant improvement was observed in 58 of 65 patients with vestibular migraine who were treated by LTG (reduction of headache, decrease of episodes of vertigo and of the dizziness handicap inventory score and increased reluctance to discontinue LTG) .…”
Section: Accumulating Evidence Suggests That Lamotrigine May Reduce Tmentioning
confidence: 99%